A sensitive and robust analytical method for the determination of enramycin residues in swine tissues using UHPLC–MS/MS - Sun, Feifei; Qiu, Jicheng; Kong, Jingyuan; Cao, Yuying; Li, Lin; Cao, Xingyuan (Frontiers in Veterinary Science, 2024)
Enramycin, a common growth promoter utilized in chickens and pigs, is sensitive against Gram-positive bacteria, and the maximum residue limit (MRL) of enramycin set up by is 30 μg/kg. However, the methods have been reported for detecting enramycin have failed to meet the accuracy requirements, with the required limit of quantification being higher than the MRL. To address this issue, we developed a high-sensitive and robust analytical method based on ultrahigh-performance liquid chromatography coupled with mass spectrometry (UHPLC–MS/MS), to determine enramycin residues in swine tissues, including liver, kidney, pork, and fat. The ENV cartridge was selected to cleanup and enrich analytes after being extracted using a mixture of 55% methanol containing 0.2 M hydrochloric acid. With comprehensively validation, this established method was found great linearity of enramycin in each tissue, with a coefficient of variation above 0.99. Satisfactory recoveries from four different spiking levels were acquired (70.99–101.40%) while the relative standard deviations were all below 9%. The limit of quantification of enramycin in the present study is 5 μg/kg in fat and 10 μg/kg in other tissues, meeting the requirements for conducting the corresponding safety evaluation study. This method was demonstrated with excellent specificity, stability, and high sensitivity. To conclude, this novel approach is sufficiently sensitive and robust for the safety evaluation of enramycin in food products.